The Audiovisual Footprint in the Heritage of the University of Granada: History, Management and Education - García Lirio, Manuela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article analyzes the audiovisual footprint of the university heritage at the University of Granada. Through movable and inmovable property, photography, photogrammetry, cinema, material and intangible heritage, the heritage memory inherited from a university with almost five centuries of history is hidden. Its identity is transformed into the most contemporary record with the objective of preserving, disseminating and exhibiting among present generations. Its history and its recovery are narrated through different museographic initiatives for its enhacement and management through education.